Peningkatan IMTAQ Siswa SMAN 17 Pekanbaru melalui Kegiatan Membaca Yasin Bersama Mahasiswa PLP UMRI Setiap Jumat Pagi - Khairul Anshari; Imeldah Imeldah; Sudarmi Sudarmi (Jurnal Pendidikan Dirgantara, 2025)
This study explores the implementation of reading yasin every Friday morning in improving IMTAQ of students at SMAN 17 Pekanbaru. Through Yasin reading activities carried out by students of the Professional Training Program (PLP) of the University of Muhammadiyah Riau (UMRI) every Friday morning. This activity is expected to be a means to instill spiritual and moral values ​​in students, as well as strengthen the relationship between students and students in the context of community service. The method used in this service is a participatory approach, where PLP students play an active role in facilitating and organizing Yasin reading activities. The results of this activity show an increase in students' spiritual awareness, which is reflected in their enthusiasm in participating in activities, as well as an increase in positive behavior in the school environment. In addition, this activity also succeeded in creating a more harmonious and religious atmosphere at SMAN 17 Pekanbaru. Thus, this yasin reading activity can be used as one of the routine programs to support the development of students' IMTAQ in schools.